2020
DOI: 10.1002/ctpp.201900197
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics investigation of soliton propagation in a two‐dimensional Yukawa liquid

Abstract: We investigate via Molecular Dynamics simulations the propagation of solitons in a twodimensional many-body system characterized by Yukawa interaction potential. The solitons are created in an equilibrated system by the application of electric field pulses. Such pulses generate pairs of solitons, which are characterized by a positive and negative density peak, respectively, and which propagate into opposite directions. At small perturbation, the features propagate with the longitudinal sound speed, form which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
3
2
0
Order By: Relevance
“…The formation of a sharp leading edge and an elongated trailing edge is an occurrence in positive density peaks, whereas negative density peaks tend to undergo the opposite transformation. [ 17 ] These findings closely match the negative peak density patterns seen in the QLCA model, confirming that the QLCA model is accurate in predicting nonlinear collective excitations. The QLCA approach qualitatively agrees with the MD simulation results, validating its usefulness as a theoretical framework for studying these structures.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The formation of a sharp leading edge and an elongated trailing edge is an occurrence in positive density peaks, whereas negative density peaks tend to undergo the opposite transformation. [ 17 ] These findings closely match the negative peak density patterns seen in the QLCA model, confirming that the QLCA model is accurate in predicting nonlinear collective excitations. The QLCA approach qualitatively agrees with the MD simulation results, validating its usefulness as a theoretical framework for studying these structures.…”
Section: Discussionsupporting
confidence: 71%
“…It is shown that the intensity of rarefactive soliton increases with increasing the value of κ$$ \kappa $$. These predictions show a close agreement with the simulation, [ 17 ] where the intensity of negative peaked density increases with κ$$ \kappa $$ or amplitude of the perturbation.…”
Section: Numerical Simulation On Soliton‐like Profiles and Validation...supporting
confidence: 81%
See 2 more Smart Citations
“…Besides providing an intuitive way of visualizing a Stokes layer, these diagrams also allow an easy identification of features such as the depth of penetration and the wavelength. We are motivated to use space-time diagrams because they are familiar in the dusty plasma literature, not for Stokes layers, but for other purposes [40,67,68,[81][82][83][84][85][86][87][88][89], including the characterization of density waves [90][91][92][93][94][95]. Some of these authors have used the terms periodograms or periodgrams for such plots.…”
Section: Space-time Diagramsmentioning
confidence: 99%